The paralympic athlete : handbook of sports medicine and science - Vanlandewijck, Yves.; Thompson, Walter R.; IOC Medical Commission (Chichester, West Sussex, UK : Wiley-Blackwell, 2011)
This brand new Handbook addresses Paralympic sports and athletes, providing practical information on the medical issues, biological factors in the performance of the sports and physical conditioning. The book begins with a comprehensive introduction of the Paralympic athlete, followed by discipline-specific reviews from leading authorities in disability sport science, each covering the biomechanics, physiology, medicine, philosophy, sociology and psychology of the discipline. The Paralympic Athlete also addresses recent assessment and training tools to enhance the performance of athletes, part.
Introduction. Introduction to the Paralympic Movement / Sean Tweedy, P David Howe -- Paralympic Sport Science. Biomechanics / Ian Rice, Florentina J Hettinga, Justin Laferrier, Michelle L Sporner, Christine M Heiner, Brendan Burkett, Rory A Cooper -- Physiology / Yagesh Bhambhani -- Medicine / Stuart Willick, Nick Webborn -- Philosophy / Steven D Edwards, Mike J McNamee -- Sociology / P David Howe -- Psychology / Jeffrey J Martin, Garry Wheeler -- Exercise Testing and Prescription. Aerobic and Anaerobic Power / Yeshayahu b3(BShaykeb4 (BHutzler, Yoav Meckel, Judith Berzen --s Strength Training / Marco Cardinale, Lee Romer -- Nutrition, Body Composition and Pharmacology / Peter Van de Vliet, Elizabeth Broad, Matthias Strupler -- Mental Preparation / Dietmar Martin Samulski, Franco Noce, Varley Teoldo da Costa -- Best Practices. Preparation for the Paralympic Summer Games: Heat, Humidity, Pollution / t
Includes bibliographical references.
Print version record.
Keywords: Athletes with disabilities; Athletes with disabilities -- Health and hygiene; Sports for people with disabilities; Disabled Persons; Sports; Athletes; Sports Medicine; Paralympics; Sport & Recreation; GAMES -- Gambling -- Sports; SPORTS & RECREATION -- Business Aspects; SPORTS & RECREATION -- Essays; SPORTS & RECREATION -- History; SPORTS & RECREATION -- Reference; TRAVEL -- Special Interest -- Sports; Electronic books